1998
DOI: 10.2307/353854
|View full text |Cite
|
Sign up to set email alerts
|

"Other Teens Drink, but Not My Kid": Does Parental Awareness of Adolescent Alcohol Use Protect Adolescents from Risky Consequences?

Abstract: This study included 199 White mother-adolescent dyads and 144 White father-adolescent dyads. All adolescents reported regular alcohol use, yet less than one third of parents were aware of their adolescents' drinking. Parental awareness of adolescent alcohol use served to protect adolescents by moderating the relation of parents' responsiveness to episodes of drinking and driving. Aware parents were more likely than unaware parents to believe their adolescents' close friends drank alcohol. Aware mothers worried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
47
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 51 publications
(82 reference statements)
2
47
1
Order By: Relevance
“…About 50% of the parents tended to underestimate the drinking activities of their adolescent children. Bogenschneider et al (1998) reported similar levels of underestimation. Langhinrichsen et al explored correlates of parental accuracy and found that parents were less accurate for older adolescents and that single mothers were less accurate than those in two-parent households.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…About 50% of the parents tended to underestimate the drinking activities of their adolescent children. Bogenschneider et al (1998) reported similar levels of underestimation. Langhinrichsen et al explored correlates of parental accuracy and found that parents were less accurate for older adolescents and that single mothers were less accurate than those in two-parent households.…”
supporting
confidence: 63%
“…Despite its central importance, only a few studies have explored how accurate parents are in characterizing the drinking activities of their adolescents (Beck et al, 1999;Bogenschneider et al, 1998;Langhinrichsen et al, 1990). Beck et al (1999) asked older high-school students to indicate if they had ever engaged in each of five alcohol-related behaviors during the past 12 months: (1) drinking and driving, (2) drinking at home without permission, (3) drinking while out, (4) riding with a drinking driver, and (5) going to places where other adolescents were drinking.…”
mentioning
confidence: 99%
“…The latter study, however, relied on reports from parents who self-referred to the project based on stress related to their child's substance use, limiting the generalizability of the fi ndings. A third study examining the differences between aware and unaware parents with regard to youth alcohol use found signifi cantly higher mean levels of mothers' reported parental monitoring among unaware parents (Bogenschneider et al, 1998). This variable was not signifi cant once entered into multivariate analyses, however.…”
Section: Predicting Parental Awareness Of Youth Report Of Substance Umentioning
confidence: 93%
“…Only a few studies, however, have addressed this discordance by examining predictors of parental awareness (Bogenschneider et al, 1998;McGillicuddy et al, 2007;O'Donnell et al, 1998;Williams et al, 2003). These studies have generally focused on parent-and child-level predictors but have been limited in the ethnic/racial composition of their samples, suggesting the need for replication with larger diverse groups.…”
Section: Predicting Parental Awareness Of Youth Report Of Substance Umentioning
confidence: 99%
See 1 more Smart Citation